The evaluation of cognitive performance in obstructive sleep apnoea patient by using validated malay version of mini mental state examination. - Yusop, Che Yusfarina Che (2012)
Obstructive Sleep Apnoea Syndrome (OSAS) is a condition where breathing stops temporarily or gets very shallow during sleep. It is most often caused by a complete or partial blockage in the throat. Untreated, it can result in neuropsychiatric and cardiovascular sequelae. Neuropsychiatric effects may include depression and cognitive dysfunction that can disrupt professional, family, and social life. Patients with OSA may develop deficits in the cognitive domains of attention, concentration, executive function, verbal and visuospatial memory, constructional abilities, and psychomotor functioning. The validated Malay Version of MMSE is one of the instrument to assess the cognitive function. The purpose of this study is to evaluate the cognitive performance in OSA patient. To compare cognitive performance between moderate and severe OSA patient and to analyze relationship of oxygen saturation (saO2) with cognitive performance. Cross sectional study on patients age 18 to 60 years old attending sleep clinic who underwent sleep study (polysomnography) in Hospital University Sains Malaysia from August 2011 to May 2012. The consented participants who fulfilled the criterias were interviewed using a questionnaire regarding demographic data, date of polysomnography and their polysomnography result. After that, the cognitive performance was evaluated using Validated Malay Version of Mini Mental State Examination which measured five areas of cognitive function which is orientation, registration, attention and calculation, word recall and language abilities , and visuospatial. A total of 38 OSA patients participated in this study with equal distribution in each groups. In our study showed that there was a statistically significant difference between the moderate OSA group and severe OSA group on cognitive performance (p=0.04). We also found that there was no significant linear correlation between oxygen saturation and cognitive performance (p=0.27). Cognitive performance of severe OSAS patients was mildly impaired in comparison to moderate OSAS. There was no association between oxygen saturation with cognitive performances in moderate and severe OSA patients. This may be due to limitations in performing MMSE test as it is unable to identify in very minimal or extremely severe cognitive dysfunction. More sophisticated test battery are required to detect small changes in cognitive performance.